f ( x ) = <msubsup> &#x222B;<!-- ∫ --> <mrow class="MJX-TeXAtom-ORD">

Emanuel Keith 2022-06-25 Answered
f ( x ) = 0 sin x 1 + sin ( sin ( t ) ) d t
Find ( f 1 ) ( 0 )
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Blaze Frank
Answered 2022-06-26 Author has 18 answers
f ( f 1 ( x ) ) = x f ( f 1 ( x ) ) ( f 1 ( x ) ) = 1 ( f r o m   C h a i n   R u l e ) ( f 1 ( x ) ) = 1 f ( f 1 ( x ) ) ( f 1 ( 0 ) = 1 f ( f 1 ( 0 ) ) N o w ,   f r o m   t h e   o r i g i n a l   e q n , f ( x ) = 0 s i n x ( 1 + s i n ( s i n t ) ) d t f ( x ) = 1 + s i n ( s i n ( s i n ( x ) ) c o s x ( f r o m   L e i b n i t z   f o r m u l a ) L e t   f 1 ( 0 ) = y t h e n   f ( y ) = 0 ,   s o   y = 0
Just find f'(0) and then you are done.
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more